The Economics of the Global Environment Catastrophic Risks in Theory and Policy - Chichilnisky, Graciela; Rezai, Armon; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
This is the first book combining research on the Global Environment, Catastrophic Risks and Economic Theory and Policy. Modern economic theory originated in the middle of the twentieth century when industrial expansion coupled with population growth led to a voracious use of natural resources and global environmental concerns. It is uncontested that, for the first time in recorded history, humans dominate the planet, changing the planet's atmosphere, its bodies of water, and the complex web of species that makes life on earth. This radical change in circumstances led to rethinking of the foundations of human organization and, in particular, the industrial economy and the economic theory behind it. This book brings together new approaches on multiple levels: environmental sustainability requires rethinking in terms of economic theory and policy as well as the considerations of catastrophic risk and extremal events. Leading experts address questions of economic governance, risk management, policy decision making and distribution across time and space.
Part I. Catastrophic risk in economic theory -- Catastrophic Risk, Rare Events, and Black Swans: Toward an Alternative Synthesis -- Preference Representations for Catastrophic Risk Analysis -- Modeling Decisions Involving Ambiguous, Vague, or Rare Events -- Modeling Uncertainty, Context and Information Fusion via Lattice-Based Probability -- The foundations of uncertainty with black swans -- The Topology of Change -- Sustainable markets with short sales -- Part II. Ethical and welfare considerations -- Sustainable recursive social welfare functions -- Intergenerational equity, efficiency, and constructability -- Sustainable exploitation of a natural resource: a satisfying use of Chichilnisky's criterion -- The axiomatic approach to the ranking of infinite streams -- Part III. The environment in a global context -- Nested externalities and polycentric institutions: must we wait for global solutions to climate change before taking actions at other scales? -- Capital growth in a global warming model: will China and India sign a climate treaty? -- Unspoken ethical issues in the climate affair: Insights from a theoretical analysis of negotiation mandates -- Carbon leakages: a general equilibrium view -- Part IV. The case of climate change -- Chaos Control - Climate Stabilization by Closing the Global Carbon Cycle -- Climate Change and Social Choice Theory -- Discounting and the evaluation of climate policy -- Global warming and economic externalities -- Part V. Economic policy and regulation -- Detrimental externalities, pollution rights, and the "Coase theorem" -- Taxes versus quantities for a stock pollutant with endogenous abatement costs and asymmetric information -- Walrasian prices in markets with tradable rights -- Part VI. Catastrophic risk in economic practice -- Exploring the role of emotions in decisions involving catastrophic risks: Lessons from a double investigation -- How the change of risk announcement on catastrophic disaster affects property prices -- Modeling US stock market volatility-return dependence using conditional Copula and quantile regression -- Economic Crises: Natural or Unnatural Catastrophes? .
Keywords: Economic theory; Political economy; International Political Economy